THE USE OF AUTHENTIC MATERIALS IN ENGLISH LANGUAGE CLASSROOM (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article discusses the problems of using authentic materials for foreign language teaching. Using authentic materials in the classroom is a useful tool for motivating students and making them comfortable using a foreign language. Authentic materials, when properly used in authentic learning environments, can have a wide range of uses in language teaching, even though they were not specifically designed for language teaching. For this reason, foreign language teachers need to expose students to authentic materials in a constructivist learning environment. In addition, in order to provide examples of future foreign language teachers using real materials in their own classes, it is necessary to create a learning environment using real materials when training future foreign language teachers. In this way, teachers-to-be are given the opportunity to see and experience first-hand the benefits and caveats of these materials. The purpose of this study is to focus on the importance and use of authentic materials in foreign language teacher education and to make some suggestions in this regard.